Improvement of a pre fabricate biogas digester tank - Mohd Abu Zar, Bahri (2012)
This project is about improvement of a prefabricated biogas digester tank to fermentation of waste product in order to produce and collect methane gas. The biogas digesters are used to produce methane gas and the designs of the digesters are commonly bigger in size and have concentration pressure gas at some area such as at the edge of the tank. The effect of concentrated pressure at the edge of the biogas digester tank will cause leakage. To produce and collect the methane gas, this biogas digester design is suitable to use at home and it is portable. So, based on the objective of this project is which to help them, a biogas digester is designed by considering the ergonomic factors for the usage of people. After the design process is completed, it is needed to be transform into the real product. The materials used to fabricate this product are round hollow steel, square hollow steel, sheet mild steel and wood. The processes involved are welding, rolling, and grinding, fastening and using glue to assemble all the parts